Tribology study on nanosilica-filled polyurethane (PU) composite coating on polypropylene substrate / Nurehan Syamimi Ismail - Nurehan Syamimi, Ismail (2012)
Acrylic based polyurethane coatings with nanoparticles embedded were prepared. The effects of nanoparticles of silica as fillers in the epoxy composite systems on tribological properties have been discussed in this article. The dispersed of nanosilica in polyurethane solution were prepared under magnetic stirring and various amounts of nanosilica powders were added so that the amount would turn out to be 3, 7 and 10% by weight respectively. The reference control was a pure polyurethane film with no nano silica content. The tribological tests were carried out by sliding against stainless steel in a pin on plate contact mode for friction and wear tester under a dry and clean condition. The sliding performs at rotary speed of 100 rpm and 200 rpm with 0.1kg to 0.4kg load with 0.1N interval, sliding for 10 minutes time. The effect of coating composition on friction and wear behaviour of composite coatings and the worn surface after testing then was observed by using optical microscope. The coating film seemed to be continuous and homogeneous since no agglomerates occur. Lower and optimum content of 3.0 wt% nanoSiO2 filled PU give the lowest friction and wear rate when the applied load and speed were increased. Keywords : acrylic based polyurethane, nanocomposite coating, friction and wear behaviour